2020
DOI: 10.1186/s12877-020-01592-x
|View full text |Cite
|
Sign up to set email alerts
|

Older adults’ preferences for, adherence to and experiences of two self-management falls prevention home exercise programmes: a comparison between a digital programme and a paper booklet

Abstract: Background: Fall prevention exercise programmes are known to be effective, but access to these programmes is not always possible. The use of eHealth solutions might be a way forward to increase access and reach a wider population. In this feasibility study the aim was to explore the choice of programme, adherence, and self-reported experiences comparing two exercise programmesa digital programme and a paper booklet. Methods: A participant preference trial of two self-managed fall prevention exercise interventi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…The PB was based on the Otago Exercise Programme [ 16 ], the DP exercises were similar but expanded with both easier and more challenging exercises inspired by the Falls Management Exercise Programme (FaME) [ 17 ]. The digital programme (Safe Step v1 web-based or mobile application) was accessed by computer, smartphone or tablet [ 8 , 18 , 19 ]. The exercises were presented in short video clips with verbal instructions and organized into ten predetermined groups of balance, strength, and step/gait exercises, all including several exercise alternatives of various difficulty to choose from.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PB was based on the Otago Exercise Programme [ 16 ], the DP exercises were similar but expanded with both easier and more challenging exercises inspired by the Falls Management Exercise Programme (FaME) [ 17 ]. The digital programme (Safe Step v1 web-based or mobile application) was accessed by computer, smartphone or tablet [ 8 , 18 , 19 ]. The exercises were presented in short video clips with verbal instructions and organized into ten predetermined groups of balance, strength, and step/gait exercises, all including several exercise alternatives of various difficulty to choose from.…”
Section: Methodsmentioning
confidence: 99%
“…Further detailed description of the interventions can be found in the Supplementary Table (S 1 ), Template for Intervention Description and Replication (TIDieR) checklist. In a previously published paper on adherence [ 19 ] more details about this feasibility study is reported.…”
Section: Methodsmentioning
confidence: 99%
“…Mansson et al's study found that, in self-administered interventions for fall prevention, the elderly who adopted the corresponding technology showed higher satisfaction than those who do not use technology. Compliance appeared to facilitate regular exercise after the intervention period [55]. The improvement of compliance reflects the utility and potential of this technology in terms of application.…”
Section: Subjective Factorsmentioning
confidence: 84%
“…The older the elderly, the worse their performance [12,28,[44][45][46] Education level Populations with a high education level tend to use new technology [28,47] Region Compared to urban residents, rural ones are not likely to use new technology [48] E-health literacy E-health literacy is considered as a prerequisite of using mobile health app [5,15,30,47,49] Information literacy People skilled in computer and Internet use tend to adopt IHMT [13,14,38,46] Ethnicity and language Ethnic and linguistic differences affect users' acceptance and use behavior [13,44] Physical difficulties Physical difficulties are an obstacle for the elderly to accept new technologies [9] Self-efficacy People with high efficacy are more willing to accept new technology [11,13,16,30,39,45,[49][50][51] Compliance Procedures/equipment that can improve compliance are easy to be continuously used [19,24,29,[52][53][54][55] Skeptical attitudes Skepticism is a barrier to the elderly using new technology [12] Perceived demand Perceived demand is an essential factor in promoting the use of intelligent health management devices [8,21,56] 1. Objective factors…”
Section: Agementioning
confidence: 99%
“…This qualitative study involved participants using this digital program, and it presents the findings of individual and focus group interviews, as well as open-ended responses to questionnaires, all of which were part of the feasibility study conducted in Umeå, Sweden (ClinicalTrials.gov NCT02916849) between September 2016 and February 2017. The feasibility study compared two home-based self-management exercise programs (a digital program [Safe Step v.1] and a paper booklet) [ 21 ]. Participants who enrolled in the study could choose the digital program or the paper booklet.…”
Section: Methodsmentioning
confidence: 99%